Teachers' capacity to care and students' well-being-evidence from empirical research - Tran, Thi Tu Anh (Vietnam National University, Hanoi, 2020)
In the current educational environment, where schools are trying to increase student well being through social -emotional learning programs with a diminishing budget, tearchers' well-being has been still neglected. Educators typically receive litle training and support for implementation and dor supporting studens' social and emotional development and evern less training and support for educators' own social and emotional development and evern lesss training and suppor for educator own social and emotional competencies